Developing Specialization Model Applications for High School Students - Triyanto, Agus; Dewanti, Septinda Rima; Sari, Widya Juwita (Jurnal Kajian Bimbingan dan Konseling, 2021)
This study aims to produce a model application of specialization for the majors of high school students. The research method used is the Borg and Gall development research method. The research procedure was carried out by conducting a literature review and preliminary study, planning, developing, validating, revising, testing on research subjects, revising, and finalizing and socializing the application specialization model. The research instrument used is a rating scale. Data analysis was carried out by averaging expert judgments on applying the specialization model that had been developed. In addition, data were also obtained from the results of student interest. The expert test results showed that the application of the specialization model for the majors of high school students that was developed was feasible to be used to provide recommendations for students’ specialization. Data from students when using the specialization model is grouped into two types of data, namely appropriate and inappropriate. The results of the trial using the specialization model by students showed that 97 percent of the subjects stated that the conclusions of the specialization model were in accordance with their interests.